The impact of taxation on bank profits: Evidence from EU banks - Chiorazzo, Vincenzo; Milani, Carlo (Journal of Banking & Finance, 2011)
Using bank-level data for the period 1990–2005, we investigate to what extent European banks are able to shift their tax-burden forward. We examine the effects of corporate income tax (CIT) and value added tax (VAT) on pre-tax profits and their components, and find that both are shifted forward. The pass-through mainly involves total operating income, but as far as CIT is concerned it also affects loss provisions, with negative implications on stability of the banking systems.